2024
DOI: 10.3390/ijms25010640
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Metabolism Modulation during SARS-CoV-2 Infection: A Spotlight on Extracellular Vesicles and Therapeutic Prospects

Heloisa D’Avila,
Claudia Natércia Rocha Lima,
Pollianne Garbero Rampinelli
et al.

Abstract: Extracellular vesicles (EVs) have a significant impact on the pathophysiological processes associated with various diseases such as tumors, inflammation, and infection. They exhibit molecular, biochemical, and entry control characteristics similar to viral infections. Viruses, on the other hand, depend on host metabolic machineries to fulfill their biosynthetic requirements. Due to potential advantages such as biocompatibility, biodegradation, and efficient immune activation, EVs have emerged as potential ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 159 publications
0
4
0
Order By: Relevance
“…Taken together, viral infection may reduce adipocyte size in SAT and VAT, and vaccination has no effect on the adipocyte size area. Studies on COVID-19 patients have shown dysregulated lipid profiles, which are associated with an increased risk of severe consequences [ 10 , 20 , 21 , 22 ]. It has been suggested that modulation of cellular lipid metabolism could be a therapeutic target for SARS-CoV-2 infection [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, viral infection may reduce adipocyte size in SAT and VAT, and vaccination has no effect on the adipocyte size area. Studies on COVID-19 patients have shown dysregulated lipid profiles, which are associated with an increased risk of severe consequences [ 10 , 20 , 21 , 22 ]. It has been suggested that modulation of cellular lipid metabolism could be a therapeutic target for SARS-CoV-2 infection [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on COVID-19 patients have shown dysregulated lipid profiles, which are associated with an increased risk of severe consequences [ 10 , 20 , 21 , 22 ]. It has been suggested that modulation of cellular lipid metabolism could be a therapeutic target for SARS-CoV-2 infection [ 20 , 22 ]. However, the influence of the infection on lipid metabolism, lipolysis, and lipogenesis in adipocytes remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may represent the cellular changes induced by the virus to facilitate its replication, as demonstrated in recent in vitro studies [ 68 , 69 ]. The virus may exploit endogenous lipid components in various forms (i.e., lipoproteins and exosomes) as “Trojan horses” to facilitate immune evasion in their systemic dissemination [ 70 , 71 ]. In contrast, SARS-CoV-2-infected CFTR KO cells exhibited fewer lipid droplets scattered in the cytoplasm than their mock-infected counterparts, which were not identifiable as lipolysosomes due to the absence of an external membrane.…”
Section: Discussionmentioning
confidence: 99%
“…These structures, derived from LDs or other cellular membranes, serve as protective compartments for viral RNA replication. The association with LDs helps shield viral RNA molecules from host immune responses [73].…”
Section: Ld and Viruses In Generalmentioning
confidence: 99%